Eficácia da ciclosporina no controle da dermatite atópica em cães - Neto, Adriano Souza; de Farias, Marconi R.; Pimpão, Claudia T.; Quitzan, Juliany G. [UNESP]; Anater, Amanda (FapUNIFESP (SciELO), 2017)
Atopic dermatitis is an itchy, chronic inflammatory skin disease of genetic origin, resulting from loss of the physical barrier function of the skin and hyper-reactivity to environmental allergens, trofoallergens, microbial allergens and to primary irritants. The efficacy of cyclosporine in the control of pruritus and lesions associated with atopic dermatitis in dogs was evaluated. Twenty-four dogs with atopic dermatitis were selected, based on Favrot et al.'s criteria (2010). They were divided into two groups of 12 dogs, where Group 1 received cyclosporine (5mg/kg/vo/24h), and Group 2 was treated with prednisone (0.5mg/kg/ vo/24h) in decreasing doses, both for 60 days. The animals were continuously evaluated, and theirits lesional symptomatology scores were based on a Cadesi-03 scale, set on days 0, 30 and 60. Pruritus scores of each dog, based on Rybnicek's criteria, were weekly evaluated, from day 0 to day 63. All collected data were analyzed by the nonparametric Kruskal- -Wallis' test, followed by Dunn's test, and for the analysis between the groups, considered the minimum significance level of 5%, t-test was used. Cyclosporin had similar efficacy in lesional control in the group which received prednisone on day (+30) (p < 0.05) and on the day (+60) (p < 0.001) of treatment, compared with day zero. A significant difference of the itching score was observed on days +28, +35, +42, +49, +56 and +63 (p < 0.001), and on day +21 (p < 0.01) when compared to initial treatment. However, its efficacy was lower than Group 2, from 42 days of evaluation on, keeping such difference on days +49, +56 and +63 (p > 0.05). Although cyclosporin have been less effective in controlling itching, it remained at acceptable levels, and its continued use was not associated with significant side effects.
Efficacy of cyclosporine in the control of atopic dermatitis in dogs
Keywords: CADESI; Corticoid; Cyclosporine; Dermatitis; Dogs; Genodermatosis; Pruritus; Rybnicek